Randomized, controlled clinical two‐centre study using xenogeneic block grafts loaded with recombinant human bone morphogenetic protein‐2 or autogenous bone blocks for lateral ridge augmentation. (13th December 2017) - Thoma, Daniel S.; Payer, Michael; Jakse, Norbert; Bienz, Stefan P.; Hüsler, Jürg; Schmidlin, Patrick R.; Jung, Ui‐Won; Hämmerle, Christoph H.F.; Jung, Ronald E.
Abstract: Objectives: To test whether or not the use of a xenogeneic block loaded with recombinant human bone morphogenetic protein‐2 (rhBMP‐2) results in different bone quantity and quality compared to an autogenous bone block. Materials and Methods: Twenty‐four patients with insufficient bone volume for implant placement were randomly assigned to two treatment modalities: a xenogeneic bone block loaded with rhBMP‐2 (test) and an autogenous bone block (control). The horizontal ridge width was evaluated prior to augmentation, after augmentation and at 4 months. Patient‐reported outcome measures (PROMs) were assessed at suture removal and at 4 months. Biopsies were obtained at 4 months and histologically evaluated. Intergroup comparisons were tested by a two‐sided Wilcoxon–Mann–Whitney test, intra‐group comparisons were performed with Wilcoxon‐signed rank test, and all categorical variables were tested with Chi‐squared tests. Results: One autogenous bone block failed. This patient was replaced, and in all subsequently treated 24 patients, implant placement was possible 4 months later. The median ridge width increased from 4.0 mm (Q1 = 2.0; Q3 = 4.0) (test) and 2.0 mm (Q1 = 2.0; Q3 = 3.0) (control) to 7.0 mm (Q1 = 6.0; Q3 = 8.0) (test) and 7.0 mm (Q1 = 6.0; Q3 = 8.0) (control) at 4 months (intergroup p > .05). A higher morbidity was reported at the augmented site in the control group during surgery. Sensitivity was more favourable in the test than that in the control group at 4 months. The biopsies revealed more mineralized tissue in the control group ( p < .0043). Conclusions: Both treatment modalities were successful in regenerating bone to place dental implants. PROMs did not reveal any significant differences between the groups except for pain during surgery at the recipient site (in favour of the test group). Histologically, a higher amount of mineralized tissue was observed for the control group at 4 months.